Studying the conduction mechanism of stabilised zirconias by means of molecular dynamics simulations - Marrocchelli, Dario (The University of Edinburgh, 2010)
Stabilised zirconias have a remarkable variety of technological and commercial applications, e.g., thermal barrier coatings, gas sensors, solid oxide fuel cells, ceramic knives and even fashion jewelry. This amazing versatility seems to originate from the creation of atomic defects (oxide ion vacancies) in the zirconia crystal. Indeed, these vacancies, and their interactions with other vacancies or cations, dramatically affect the structural, thermal, mechanical and electrical properties of zirconia. This thesis is concerned with the study of the role of the vacancy interactions on the conducting properties of these materials. This study was performed by using realistic, first-principles based molecular dynamics simulations. The first system studied in this thesis is Zr0:5􀀀0:5xY0:5+0:25xNb0:25xO7. This has a fixed number of vacancies across the series but its conductivity changes by almost two orders of magnitude as a function of x. For this reason, Zr0:5􀀀0:5xY0:5+0:25xNb0:25xO7 represents an ideal test-bed for the role of the cation species on the defect interactions and therefore on the ionic conductivity of these materials. Realistic inter-atomic potentials for Zr0:5􀀀0:5xY0:5+0:25xNb0:25xO7 were developed on a purely first-principles basis. The observed trends of decreasing conductivity and increasing disorder with increasing Nb5+ content were successfully reproduced. These trends were traced to the influences of the cation charges and relative sizes and their effect on vacancy ordering by carrying out additional calculations in which, for instance, the charges of the cations were equalised. The effects of cation ordering were considered as well and their influence on the conductivity understood. The second part of this thesis deals with Sc2O3–doped (ScSZ) and Y2O3–doped (YSZ) zirconias. These systems are of great academic and technological interest as they find use in solid oxide fuel cells. Inter-atomic potentials were parametrised and used to predict the structural and conducting properties of these materials, which were found to agree very well with the experimental evidence. The simulations were then used to study the role of the vacancy interactions on the conducting properties of these materials. Two factors were found to influence the ionic conductivity in these materials: cation-vacancy and vacancy-vacancy interactions. The former is responsible for the difference in conductivity observed between YSZ and ScSZ. Vacancies, in fact, prefer to bind to the smaller Zr4+ ions in YSZ whereas there is not a strong preference in the case of ScSZ, since the cations have similar sizes in this case. This effect is observed at temperatures as high as T = 1500 K. Finally, it was found that vacancies tend to order so that they can minimise their mutual interaction and that this ordering tendency is what ultimately is responsible for the observed anomalous decrease of the ionic conductivity with increasing dopant concentration. The consequences of such a behaviour are discussed.
Keywords: zirconia; oxide ion vacancies; conduction; solid oxide fuel cells; ionic conductivity